SEELISCHE UNBEFANGENHEIT – DAS KIND ALS WAHRER MYSTKIER IM ZEICHEN DER “BLAUEN BLUME” BEI NOVALIS UND PHILIPP OTTO RUNGE - Sebesta, Jadwiga; Wawrzynek, Karin (Studia Europaea Gnesnensia, 2014)
The aim of this article is to show the role of an innocent child as the true mystic, which formally represents the completion of the “Blue Flower”, the main symbol of the German Age of Romanticism, the epoch of yearning for the infinity, inner unity, love and redemption. These aspirations, encapsulated in the notion of the innocent child as the true mystic is particularly manifest in the literary works of Novalis and the paintings of Philipp Otto Runge.